2005
DOI: 10.1021/jf0518352
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Australian Olive Mill Waste for Recovery of Biophenols

Abstract: Olive mill waste is a potential source for the recovery of phytochemicals with a wide array of biological activities. Phytochemical screening of hexane, methanol, and water extracts revealed a diversity of compounds, perhaps overlooked in previous studies through intensive cleanup procedures. Methanol and water extracts contained large amounts of biophenols, and further testing of polar extraction solvents, including ethyl acetate, ethanol, propanol, acetone, acetonitrile, and water/methanol mixtures, highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 25 publications
3
149
1
7
Order By: Relevance
“…Therefore, water extracts were spiked with different concentrations of sterile ascorbic acid (AA) and Na 2 EDTA (EDTA) solutions, and samples were incubated for 15 days. Acteoside decomposition was quantified from samples, the results are plotted in (Obied et al, 2005), who found that oxygen was essential for acteoside degradation in an olive mill waste model system, and phenolic compounds' recovery could be enhanced by addition of the antioxidant sodium metabisulphite. Antioxidants were also shown to inhibit decomposition of CA derivates in Echinacea (Chantal Bergeron, 2002).…”
Section: 4mentioning
confidence: 99%
“…Therefore, water extracts were spiked with different concentrations of sterile ascorbic acid (AA) and Na 2 EDTA (EDTA) solutions, and samples were incubated for 15 days. Acteoside decomposition was quantified from samples, the results are plotted in (Obied et al, 2005), who found that oxygen was essential for acteoside degradation in an olive mill waste model system, and phenolic compounds' recovery could be enhanced by addition of the antioxidant sodium metabisulphite. Antioxidants were also shown to inhibit decomposition of CA derivates in Echinacea (Chantal Bergeron, 2002).…”
Section: 4mentioning
confidence: 99%
“…The extraction efficiency of hydroxycinnamic acids from olive mill waste was highest when 50% v/v aqueous solutions of ethanol, propanol, ACN and acetone were used [85]. The two-phase decanter method preserved more of the phenolic content than the three-phase method by which the oil, water and husk is separated from the olive paste [84].…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 99%
“…The following aspects are mentioned in the papers: Storage under different conditions [3, 14, 16, 20, 23, 40, 41 -43, 46, 49, 53, 63, 67, 68, 70, 74, 75, 77 -80, 83, 91, 100, 102], washing treatment [78,104], blanching [59,65,101], drying [102], sun-drying [37,45], treatment with a growth regulator [23,41], alkaline and acid hydrolysis [90], juice centrifugation [65], flash release process [54], cowinemaking and wine aging [52,56,105], grape destemming [17], fermentation [44,57], germination [22,82,93], extraction [60,84,85,89], thermal stability [44], bread making [86], cooking [22], roasting [97], stir-baked processing [96], steaming [87], thermal treatment [50,58,68,81], SO 2 treatment [106], break-process [72], freezing [4,71], freeze-drying [64], maceration [47,48,51], enzymatic treatment …”
Section: Aspects Of Postharvest Processing and Storage Proceduresmentioning
confidence: 99%
See 2 more Smart Citations